The Main Directions of Development of Innovative Activity in Enterprises - Mamurjon Ahmadjonovich Jurabekov (Research Parks Publishers, 2021)
Although the study of innovation processes may seem realistic, it shows that only one hundredth of all ideas, and in some cases one in a thousand, lead to commercial success. So, in order for an idea to be effective on the one hand, and on the other hand, it is necessary to consider many proposals. The impact of innovation on firm performance has been a matter of significant interest to economists and policy makers for decades. This article examines the main directions of the development of innovative activities in enterprises, in which current problems and future prospects are studied.